Continuous Monitoring Reveals Protective Effects of N‐Acetylcysteine Amide on an Isogenic Microphysiological Model of the Neurovascular Unit. Issue 32 (26th June 2021) - Matthiesen, Isabelle; Voulgaris, Dimitrios; Nikolakopoulou, Polyxeni; Winkler, Thomas E.; Herland, Anna
Abstract: Microphysiological systems mimic the in vivo cellular ensemble and microenvironment with the goal of providing more human‐like models for biopharmaceutical research. In this study, the first such model of the blood‐brain barrier (BBB‐on‐chip) featuring both isogenic human induced pluripotent stem cell (hiPSC)‐derived cells and continuous barrier integrity monitoring with <2 min temporal resolution is reported. Its capabilities are showcased in the first microphysiological study of nitrosative stress and antioxidant prophylaxis. Relying on off‐stoichiometry thiol–ene–epoxy (OSTE+) for fabrication greatly facilitates assembly and sensor integration compared to the prevalent polydimethylsiloxane devices. The integrated cell–substrate endothelial resistance monitoring allows for capturing the formation and breakdown of the BBB model, which consists of cocultured hiPSC‐derived endothelial‐like and astrocyte‐like cells. Clear cellular disruption is observed when exposing the BBB‐on‐chip to the nitrosative stressor linsidomine, and the barrier permeability and barrier‐protective effects of the antioxidant N ‐acetylcysteine amide are reported. Using metabolomic network analysis reveals further drug‐induced changes consistent with prior literature regarding, e.g., cysteine and glutathione involvement. A model like this opens new possibilities for drug screening studies and personalized medicine, relying solely on isogenic human‐derived cells and providing high‐resolution temporal readouts that can help in pharmacodynamic studies. Abstract : Microphysiological systems show great potential to complement or supersede animal‐based studies or traditional cell culture in biomedical research. An isogenic human induced pluripotent stem cell (hiPSC)‐derived on‐chip model of the blood‐brain barrier is presented, using a hydrophilic structural material that facilitates simple fabrication and integration of sensors. With continuous barrier monitoring, the prophylactic effects of N ‐acetylcysteine amide against nitrosative stress are captured.